A Naturally Occurring Point Mutation in the β3 Integrin MIDAS-like Domain Affects Differently αvβ3 and αIIbβ3 Receptor Function - Morel-Kopp, Marie-Christine; Melchior, Chantal; Chen, Ping; Ammerlaan, Wim; Lecompte, Thomas; Kaplan, Cécile; Kieffer, Nelly (Thrombosis and Haemostasis, 2001)
We have investigated the effect of a new Leu196Pro mutation, identified in the MIDAS-like domain of the β3 integrin subunit in a patient with type II Glanzmann thrombasthenia, on β3 integrin receptor function. Expression of the mutant β3Pro196 subunit in CHO cells, either associated with recombinant human αIIb or αv, resulted in normal biosynthesis of β3 and heterodimerization with αv or IIb, but selectively interfered with αIIbβ3 maturation and transport to the cell surface. Functional analysis of the β3 mutant receptors revealed strong inhibition of αvβ3-mediated cell spreading on immobilized fibrinogen, focal contact formation, p125FAK phosphorylation and fibrin clot retraction, as opposed to normal αIIbβ3-mediated cell interaction with immobilized fibrinogen, focal contact translocation and signaling. In contrast, antibody- or DTT-activated mutant αIIbβ3 was unable to bind soluble fibrinogen or the ligand mimetic PAC-1 monoclonal antibody, but underwent a conformational change following RGD peptide binding as demonstrated by AP5-LIBS epitope expression. These results suggest that (1) the highly conserved TL196T motif in the β3 integrin subunit is located in a domain structurally important for the exposure of a functional binding site for soluble fibrinogen; and (2) that the MIDAS-like contact site in β3 is not involved in αIIbβ3-mediated cell adhesion to immobilized fibrinogen, while it is essential for αvβ3-mediated interaction with this ligand.
Keywords: Glanzmann thrombasthenia; 3 integrins; fibrinogen receptor; cell adhesion